Fuzzy Availability Assessment for a Repairable Multistate Series-Parallel System. (25th June 2015) - Hu, Linmin; Yue, Dequan; Tian, Ruiling
Abstract : This paper considers a repairable multistate series-parallel system (RMSSPS) with fuzzy parameters. It is assumed that the system components are independent, and their state transition rates and performance rates are fuzzy values. The fuzzy universal generating function technique is adopted to determine fuzzy state probability and fuzzy performance rate of the system. On the basis of α -cut approach and the extension principle, parametric programming technique is employed to obtain the α -cuts of some indices for the system. The system fuzzy availability is defined as the ability of the system to satisfy fuzzy consumer demand. A special assessment approach is developed for evaluating the fuzzy steady-state availability of the system with the fuzzy demand. A flow transmission system with three components is presented to demonstrate the validity of the proposed method.